A Recombinant Vesicular Stomatitis Virus Bearing a Lethal Mutation in the Glycoprotein Gene Uncovers a Second Site Suppressor That Restores Fusion - Stanifer, Megan L. (American Society for Microbiology, 2011)
Vesicular stomatitis virus (VSV), a prototype of the Rhabdoviridae family, contains a single surface glycoprotein (G) that is responsible for attachment to cells and mediates membrane fusion. Working with the Indiana serotype of VSV, we employed a reverse genetic approach to produce fully authentic recombinant viral particles bearing lethal mutations in the G gene. By altering the hydrophobicity of the two fusion loops within G, we produced a panel of mutants, W72A, Y73A, Y116A, and A117F, that were nonfusogenic. Propagation of viruses bearing those lethal mutations in G completely depended on complementation by expression of the glycoprotein from the heterologous New Jersey serotype of VSV. The nonfusogenic G proteins oligomerize and are transported normally to the cell surface but fail to mediate acid pH-triggered membrane fusion. The nonfusogenic G proteins also interfered with the ability of wild-type G to mediate fusion, either by formation of mixed trimers or by inhibition of trimer function during fusion. Passage of one recombinant virus, A117F, identified a second site suppressor of the fusion block, E76K. When analyzed in the absence of the A117F substitution, E76K rendered G more sensitive to acid pH-triggered fusion, suggesting that this compensatory mutation is destabilizing. Our work provides a set of authentic recombinant VSV particles bearing lethal mutations in G, confirms that the hydrophobic fusion loops of VSV G protein are critical for membrane fusion, and underscores the importance of the sequence elements surrounding the hydrophobic tips of the fusion loops in driving fusion. This study has implications for understanding dominant targets for inhibition of G-mediated fusion. Moreover, the recombinant viral particles generated here will likely be useful in dissecting the mechanism of G-catalyzed fusion as well as study steps of viral assembly.